Language Combinatorics: Aspects of Studying - M. V. Vlavatskaya (Научный диалог, 2017)
The article is devoted to the identification and characterization of aspects of the language combinatorics studying. The research is conducted in the framework of combinatorial linguistics that studies the linear relations of language units and their combinatorial potential. The relevance of the topic is determined by the need to study functionally-speech aspect of the language as a whole. Special attention is paid to perspectives of studying the language combinatorics in various aspects: historical, typological, metalinguistic, cognitive, psycholinguistic, normative and functional-semantic. Within each of them the questions are raised that need to be resolved. In addition, the author determined and characterized theoretical and applied sections of combinatorial linguistics also open for study. Thus, combinatorial lexicography is defined as a theoretical and applied sub-section exploring theoretical and practical problems of lexicographical interpretation of the combinatorial syntagmatic properties of words and creation of dictionaries of combinatory type. It is noted that currently the ethnocultural combinatorial lexicography is actively developing, which aim is to capture the ethno-cultural collocations, exotic in the understanding of other cultures and peoples. In connection with the achievements of combinatorial linguistics, the author indicates the necessity of improvement of the methodology of teaching a second language. It is emphasized that such programs must provide the appeal of students to the principles of language combinatorics. It is argued that another applied sub-section of combinatorial linguistics - combinatorial linguodidactics - is intended to serve these goals.